PERANCANGAN ALAT AGRICULTURE SOIL FERTILITY DETECTION BERBASIS IOT UNTUK PEMANTAUAN PH, SUHU DAN KELEMBAPAN TANAH - Andre William; Hani Salsabilah; Dandun Widhiantoro (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Soil fertility is a major factor in maintaining soil, and accurate monitoring of soil fertility conditions is essential to increasing crop yields and efficient use of resources. In the era of Internet of Things (IoT) technology, the concept of "Agriculture Soil Fertility" has emerged as an innovative solution to monitor and manage soil fertility more precisely and efficiently. This research implements an IoT-based system for real-time monitoring of soil fertility. This device uses the ESP32 component as the main microcontroller that controls the sensors used. The sensors used are the soil pH sensor on GPIO32, the soil moisture sensor on GPIO33, and the soil temperature sensor on GPIO25. For indications that are determined to show fertility levels with 3 categories including 100% - 61% fertile, 60% - 21% less fertile, and 20% - 0% infertile